The first collections for mestizo maidens in Lima and Cusco, 1550 - 1580 - van Deusen, Nancy E. (1990)
Through the study of the recollection, an institution for women and girls still on the fringes of historical research, new insights into the social and economic mechanisms of the early colonial period can be gained. One of the first problems that the Spanish authorities and eminent citizens had to confront was that of the first generation of mestizos, children born in legal or illegal unions, generally between Spaniards and indigenous women.